Replication of the Moloney Murine Sarcoma-Leukemia Virus in XC Cells - Trowbridge, Sidneye T. (1973)
The XC rat cell line was found to support the replication of a strain of the Moloney murine sarcoma-leukemia virus. In growth curve experiments cytopathology was paralleled by the production of murine sarcoma virus and leukemia virus progeny having the biologic, antigenic, and biophysical properties of the infecting virus.